Analisis Bahasa Jurnalistik Majalah LPM Dinamika UIN Sumatera Utara Edisi 62 - Panggabean, Tri Pujiati; Rasyid, Abdul (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Language in news is a means of storing information. The accuracy of the language used determines whether the information presented is understood or not. When making news, it is very necessary to pay attention to journalistic language, because it must be understood by all levels of society. This research analyzes the use of journalistic language in LPM Dinamika UIN North Sumatra Magazine Edition 62. Is it in accordance with the 17 characteristics of journalistic language, namely simple, short, concise, direct, clear, clear, interesting, populist, logical, democratic, grammatical, avoiding speech, avoiding foreign terms, appropriate choice of diction, prioritizing active sentences, avoiding technical terms, submitting to ethical rules. The research method used is a qualitative technique, descriptive analysis approach. Based on the research results, it can be concluded that the use of journalistic language in LPM Dinamika UIN North Sumatra Magazine Edition 62 has used the characteristics of journalistic language, but errors were still found in detail: aspects of selecting appropriate diction 1, brief aspects 6, straightforward aspects 1, aspects of prioritizing active sentences 3 , democratic aspect 2, aspect of using foreign sentences 3.